Effectiveness Of Activated Carbon From Bamboo Chips For Industrial Wastewater Treatment - Muhammad Fathurrahman, Mohammad Shukor (2022)
The river system surrounding the Gebeng industrial area has been overstressed as a result of the rapid growth of production in the area, which includes a variety of factories and mining activities. Based on the effluents discharged, industrial activities based on petrochemical and bauxite mining have been listed as a contributor to chemicals and heavy metals contamination in water bodies. Heavy metals, which have been accumulating in soil for a long time, are harmful to marine ecosystems. Contamination of water with organic and inorganic compounds such as metals and pesticides has prompted researchers to improve purification and extraction methods such as pollutant adsorption using activated carbon. The aim of this study was to see how effective bamboo chip activated carbon is at treating contaminated wastewater from the Gebeng industrial region. Water's physical and chemical parameters were analysed to assess the initial pollution level, which was then compared to the level of pollution after treatment by three different ratios and two types of temperature (400°C and 500 °C). pH, turbidity, total suspended solid (TSS), biochemical oxygen demand (BOD), chemical oxygen demand (COD), as well as zinc (Zn) and copper (Cu) heavy metals (Cu) is being test. 4 litres of wastewater were treated with 20-gram,30 gram and 40 grams of activated carbon made from bamboo chip in powdered. Each parameter's pollution level was reduced to a very low concentration below the permissible standard value after the treatment. The wastewater sample was totally depleted of BOD, COD and copper. This demonstrated that activated carbon made from bamboo chip can treat contaminated waste water by absorbing pollutants. Finally, the study's findings indicate that waste bamboo chip can be converted into a high-capacity adsorbent and used to treat contaminated industrial wastewater.